Potential Prognostic Impact of Dopamine Receptor D1 (rs4532) Polymorphism in Post-stroke Outcome in the Elderly - Park, Hae-Yeon; Kim, Youngkook; Oh, Hyun Mi; Kim, Tae-Woo; Park, Geun-Young; Im, Sun (Frontiers in Neurology, 2021)
Background: Single nucleotide polymorphisms (SNPs) may affect post-stroke motor recovery, and some SNPs have been implicated in swallowing disturbances after stroke. Certain SNPs may also have altered influences according to different age. Objective: This post-hoc study investigated whether SNPs have different effects on dysphagia recovery between the elderly versus. young stroke patients. Methods: Analysis was conducted from a previous study including 218 stroke subjects with dysphagia. They were stratified into two groups, aged < 65 and aged ≥ 65 years. The primary outcome was persistence of nil per mouth (NPM) at 3-months post-stroke onset. Association between outcome and 9 different SNPs were investigated. Results: The elderly group (50%, n = 103) showed poorer swallowing outcomes than the young group. The minor allele of the dopamine receptor D1 (DRD1, rs4532) polymorphism showed potential association with an increased risk of NPM at 12-weeks post-stroke in the elderly, both in the additive (OR, 2.94; 95% CI, 1.17-7.37) and dominant models (OR, 2.93; 95% CI, 1.04-8.23) but did not reach statistical significance (P-value = 0.022). Logistic regression analysis showed that in those aged ≥ 65 years, models including the minor allele of rs4532 predicted the risk of the poor outcome with good accuracies with even after adjustment of clinical factors such as previous pneumonia episodes (AUROC, 0.86; 95% CI, 0.79-0.93) or the National Institutes of Health Stroke Scale (AUROC, 0.82; 95% CI, 0.67-0.92). In contrast, those aged < 65 years seemed not to be affected by the presence of the rs4532 polymorphism and models that included intubation history (AUROC, 0.81; 95% CI, 0.73-0.90) or previous pneumonia episodes (AUROC, 0.77; 95% CI, 0.68-0.87) showed modest levels of accuracies in predicting NPM at 12-weeks poststroke. Conclusions: Our study suggests a possible association between the rs4532 and post-stroke swallowing recovery, primarily in those aged ≥ 65 years. Certain SNPs may lead to less favourable outcomes in the elderly. The gene-age interaction should be considered in post-stroke swallowing recovery